The Efficacy and Safety of Lower-Limb Plyometric Training in Older Adults: A Systematic Review - Vetrovsky, Tomas; Steffl, Michal; Stastny, Petr; Tufano, James J (Sports medicine, 2019)
BACKGROUND: The aging process is associated with a progressive decline of neuromuscular function, increased risk of falls and fractures, impaired functional performance, and loss of independence. Plyometric training may mitigate or even reverse such age-related deterioration; however, little research on the effects of plyometric exercises has been performed in older adults. OBJECTIVE: The objective of this systematic review was to evaluate the safety and efficacy of plyometric training in older adults. METHODS: Papers reporting on randomized trials of plyometric training in older adults (≥ 60 years) and published up to December 2017 were sought in the PubMed, SPORTDiscus, Scopus, and EMBASE databases, and their methodological quality was assessed using the Physiotherapy Evidence Database (PEDro) scale. A narrative synthesis of the findings is presented in this systematic review. RESULTS: Of the 2236 identified papers, 18 were included in the review, reporting on 12 different studies with a mean PEDro score of 6.0 (range 4-7). Altogether, 289 subjects (176 females and 113 males) were included in 15 intervention groups with plyometric components (n = 8-36 per group); their mean age ranged from 58.4 to 79.4 years. The plyometric training lasted from 4 weeks to 12 months. Muscular strength, bone health, body composition, postural stability, and jump and physical performance were the most often reported outcomes. No study reported increased occurrence of injuries or other adverse events related to plyometric exercises. CONCLUSION: Plyometric training is a feasible and safe training option with potential for improving various performance, functional, and health-related outcomes in older persons.
Keywords: randomizované kontrolované studie jako téma; Randomized Controlled Trials as Topic; Middle Aged; lidé středního věku; lidé; plyometrická cvičení; senioři; Aged; dolní končetina; Lower Extremity; Plyometric Exercise; bezpečnost pacientů; Patient Safety; Humans